Interplay between bond breaking and plasticity during fracture at a nanomolecularly-modified metal-ceramic interface. (August 2016) - Kwan, Matthew; Braccini, Muriel; Jain, Ashutosh; Lane, Michael W.; Ramanath, Ganpati
Abstract: We reveal the roles of moisture and temperature on the interplay between interfacial work of adhesion γa and metal plasticity γp for copper-silica interfaces modified with an organosilane nanolayer. We find that γp ≠ 0 for interfaces with metal thicknesses hCu > 12 nm, and increases with hCu before it saturates at hCu 165 nm. For a fixed hCu, γp increases due to temperature-induced yield stress decrease despite a decrease in γa with temperature because of water-induced siloxane bond weakening. These findings should be valuable for understanding the fracture mechanics of, and designing, nanomolecularly-functionalized interfaces subject to thermomechanical and chemical stresses. Graphical abstract: